Antimycobacterial and anti-inflammatory activities of metabolites from endophytic and soil fungi - Willian Jonis Andrioli; Thatiana Lopes Bia Ventura Simão; Daniella Passos Ferreira; Marlon Heggdorne Araújo; Sanderson Dias Calixto; Jairo K. Bastos; Lucy Seldin; Elena Lasunskaia; Michelle Frazão Muzitano (Elsevier, 2022)
Background: Increased prevalence of high virulent strains of Mycobacterium tuberculosis and M. kansasii require the development of new antimycobacterial drugs safe and more effective. And, in this context, endophytic fungi have been known as prominent sources of bioactive compounds. Purpose: To study the antimycobacterial and anti-inflammatory activities of six fungal metabolites: austdiol (1), austdiol diacetate (2), mycoleptone A (3) and eugenitin (4) isolated from cultures of endophyte Mycoleptodiscus indicus; emodin (5) from endophyte Penicillium citrinum and δ-lactam (6) from soil fungi Humicola grisea. Methods: Antimycobacterial activity against M. bovis BCG, M. tuberculosis and M. kansasii strains was evaluated using MTT method to determine the MIC50. The anti-inflammatory activity and cytotoxicity assay were carried out in LPS-stimulated RAW 264.7 macrophages. Results: Emodin (5) was the most active compound against high virulent M. tuberculosis and M. kansasii strains exhibiting MIC50 of 8.2 ± 1.0 and 23.9 ± 0.9 μM respectively and against intracellular M. tuberculosis H37Rv growth (MIC50 of 6.5 ± 1.5 μM). Emodin inhibitory activity has been previously described only against extracellular M. tuberculosis strains. Azaphilones (1 and 3) also showed inhibitory activity against hypervirulent M. tuberculosis culture (MIC50 ≤ 40 μM) and intracellular growth (MIC50 ≤ 30 μM) whereas compounds 1 and 2 were active against high virulent M. kansassi strains (MIC50 ≤ 40 μM). Anti-inflammatory activity to inhibit NO, TNF-α and IL-1β production on LPS-stimulated macrophages was observed notably for austdiol (1) and emodin (5) with MIC50 ≤ 10 μM and good potential for compounds 2 and 3. Conclusion: Azaphilone compounds (1, 2 and 3) and emodin (5) exhibiting both activities, antimycobacterial and anti-inflammatory, being promising anti-TB agents for further investigations focusing on dual treatment of severe pulmonary TB and NMT infections associated to hyperinflammation.